Fabrication and mechanical properties of hydroxyapatite filled polyetheretherketone functional gradient biomaterials. (1st March 2016) - Pan, Yusong; Chen, Yan; Shen, Qianqian; Pan, Chengling
Abstract : Hydroxyapatite filled polyetheretherketone functional gradient biomaterials (HA/PEEK FGBm) were fabricated through layer‐stacking method and in combination with hot press moulding technology. The influences of total HA content, HA concentration difference between adjacent layers (HCDBAL) and annealing treatment on the tensile properties of HA/PEEK FGBm were investigated. The results indicated that the tensile strength and tensile fracture strain of HA/PEEK FGBm decreased with the increasing total HA content. Contrarily, the tensile modulus of HA/PEEK FGBm increases with the rise of total HA content. The tensile strength and modulus of the HA/PEEK FGBm first increased and then decreased with the rise of HCDBAL. Such change in behaviour was more obvious for the HA/PEEK FGBm with 30% total HA content. Furthermore, the tensile strength and modulus of the HA/PEEK FGBm were obviously improved after annealing treatment.